The importance of diabetic foot management / Wan Syazehan Ruznan and Mohd Khairi Mohd Yusoh - Ruznan, Wan Syazehan; Mohd Yusoh, Mohd Khairi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Diabetes mellitus prevalence and its associated complications have become increasingly common and growing rapidly throughout most the Asian countries. The diabetes prevalence in 2003 was high in Singapore (12.3%), Brunei (10.7%), Malaysia (9.4%) and Hong Kong (8.8%) with estimated increment from 3 to 7% by 2025. Malaysia, being situated at the equator line, experiences hot and humid weather throughout the whole year. Some countries (e.g. Malaysia, Singapore, Brunei and Hong Kong) show higher increment of diabetes mellitus prevalence as economic development and urbanisation (due to natural population growth, expansion of urban areas and rural to urban migration) lead to changing lifestyles with reduced physical activity and increased obesity in the whole population (Cockram, 2000).